The Impact of Discipline and Occupational Safety and Health (K3) on Employee Performance in The Preparation Division PT Victory Chingluh Indonesia - Suganda, Erik; Arif, Fathan (STEBIS Bina Mandiri, 2025)
This study aims to analyze the impact of discipline and OHS on employee performance at PT Victory Chingluh Indonesia. This study is motivated by the importance of quality human resources in supporting company productivity, as well as the discovery of performance fluctuations and a fairly high level of absenteeism in the company. The approach used is quantitative with a saturated sample method, involving the entire population of 65 respondents. Data collection techniques were carried out through questionnaires, while data analysis techniques used classical assumption tests, multiple linear regression analysis, t-tests and F-tests, and coefficients of determination. The results of the study indicate that discipline and OHS have a positive and significant effect on employee performance. This is evidenced by the regression equation Y = 1.181 + 0.477 X1 + 0.599 X2. The t-test shows that discipline (X1) has a significant influence on employee performance (Y) with a calculated t value > t table (16.715 > 1.669), and K3 (X2) also shows a significant influence with a calculated t value > t table (19.086 > 1.669), both with significance <0.05. The F test states that simultaneously both independent variables have a significant influence on employee performance with F count 220.209 > F table 3.14 and significance 0.001 <0.05. This study concludes that increasing discipline and improving K3 needs to be continuously carried out to increase employee performance productivity.